Natural spread of mycoviruses a puzzling and dazzling issue for biocontrol of chestnut blight by Cryphonectria Hypovirus - Gouveia, Maria Eugénia (2022)
Mycoviruses are widespread viruses in filamentous fungi considered ubiquitous in all groups. Cryphonectria hypovirus 1 (CHV1) of the Hypoviridae family is included in the genus Hypovirus. Hypovirus are well-studied biological control agent of chestnut blight a lethal disease of Castanea sativa Mill. Unlike many mycoviruses, which are cryptic or latent in their host, CHV1 reduce virulence, reduce pigmentation and sporulation and induce female sterility in its host the Cryphonectria parasitica fungus. Chestnut blight was introduced in Portugal and rapidly became a severe lethal disease in all chestnut regions in the 90’s. Initial epidemics had a very rapid spread and no or few cases of hypovirulence was reported. Besides scientific issues are obtained therapeutic hypovirulence was introduced as a biological control to mitigate disease impact. Later, in 2013 chestnut blight appears in scattered stands of the coast north Minho region where natural spread is the dominant way of hypovirulence spread. In this study we investigate and specifically addressed the question of the massive natural spread of hypovirulence. We studied vegetative compatibility system (vic genes) of the host fungus, presence and characterization of CHV1 subtypes and hypovirus transmission capacity, issues that play a key role in hypovirus spread. Although some different results are obtained major key determinants and driven forces to improve natural hypovirus spread are still unclear and new approaches as (HTS) high throughput sequencing will be valuable to understand the driven forces of natural dissemination that will greatly increase field sustainability of therapeutic applications of hypovirulence and chestnut recovered